Problem Pengolahan Data Gaya Berat Mikro antar Waktu - Supriyadi S (Department of Physics, Sebelas Maret University, 2016)
At time lapse microgravity survey will be got data in place for difference period. The Anomaly caused by subsidence and density change under surface which related to groundwater level change. This matter become problem when will take one of the anomaly sources to processed is furthermore. Reduction one of anomaly source cannot be done direct but must be done with filtering process. Process filtering done by using FFT (Fast Fourier Transform), its principal is to move data from time domain to frequency domain. At frequency domain this is mathematics process conducted. On subsidence case study in Semarang by using this technique indicate that subsidence value from time lapse micro gravity survey have tendency is equal to result from geodesy survey.